Overview of the Ferdina-like Goniasteridae (Echinodermata: Asteroidea) including a new subfamily, three new genera and fourteen new species - Mah, Christopher L. (Zootaxa, 2017)
Recent assignment of some goniasterid-like Ophidiasteridae into the Goniasteridae has led to further re-evaluation of other ophidiasterids as possible goniasterids. This led to the discovery of new genera and species supported by a distinctive set of characteristics which support a new subfamily, the Ferdininae, a group originally outlined by Marsh and Price (1991) within the Goniasteridae. The historical Ophidiasteridae is paraphyletic and includes several nominal ophidiasterid genera (e.g., Fromia, Neoferdina, etc.). Newly described material has led to the inclusion of six genera,within this group, of which three, Bathyferdina n. gen., Eosaster n. gen., and Kanakaster n. gen., are newly described. Fourteen new species in five genera are described. This includes Bathyferdina aireyae n. gen., n. sp., Eosaster nadiae n. gen., n. sp., Ferdina mena n. sp., Kanakaster balutensis n. gen., n. sp., Kanakaster convexus n. gen., n. sp., Kanakaster discus n. gen., n. sp., Kanakaster larae n. gen., n. sp., Kanakaster plinthinos n. gen., n. sp., Kanakaster solidus n. gen., n. sp., Neoferdina annae n. sp., Neoferdina antigorum, n. sp., Neoferdina momo, n. sp., Neoferdina oni, n. sp., and Paraferdina plakos, n. sp. Identification keys, synopses, and description of these taxa are included.